ANTS™: A BIOLOGICALLY‐INSPIRED MODEL FOR AGILE CYBER DEFENSE. Issue 2 (July 2016) - Crane, Earl
ABSTRACT: Current cyber security defenses are failing from increased scale and complexity. Cyber defenders and executive leadership struggle to secure what matters most to prevent the next inevitable breach. For inspiration, we look to ants as a survivable and resilient ecosystem, defining an appetite for cyber risk, a model for distributed communication about what makes us nervous, and simple characteristics inspired by the ant for agile cyber defense.